High‐resolution colonic manometry accurately predicts colonic neuromuscular pathological phenotype in pediatric slow transit constipation. Issue 1 (3rd October 2012) - Giorgio, V.; Borrelli, O.; Smith, V. V.; Rampling, D.; Köglmeier, J.; Shah, N.; Thapar, N.; Curry, J.; Lindley, K. J.
Abstract Background Severe pediatric slow transit constipation (STC) is commonly due to intrinsic colonic neuromuscular disease. We sought to correlate neuromuscular histological phenotypes in pediatric STC with colonic manometric phenotypes using high‐resolution manometry (HRM). We tested the hypothesis that failure of motor quiescence (FQ) between bisacodyl‐induced high amplitude propagating sequences (HAPSs) might predict neuromuscular pathology. Methods Eighteen children (10 males, median age: 7.5 years) with refractory STC underwent stationary colonic HRM before segmental colonic resection. Six age‐matched constipated children with normal colonic transit served as controls. Colonic resection specimens underwent histopathological analysis. Conventional manometric parameters and area under the curve (AUC) during a 1‐min period following bisacodyl‐induced HAPSs [PBAUC1], as measure of FQ, were calculated. Key Results Numbers of postbisacodyl HAPSs in descending and sigmoid segments were lower in patients than controls (P < 0.01, respectively). Low amplitude propagating sequences (LAPSs) were common prebisacodyl in controls and rare in STC (P < 0.001), whereas postbisacodyl LAPS were more common in STC (P < 0.001). Postbisacodyl, both retrograde propagating contractions and bursts of contractions were present in STC patients only (P < 0.001 and P < 0.01). Postbisacodyl simultaneous pressurization was seen only in STC (P < 0.05 and P < 0.001, in descending and rectosigmoid segments). Histological abnormalities were present in 17/18. Fourteen were neurogenic, one neuro‐myogenic, and two myogenic. In segments with HAPS, PBAUC1 was predictive of colonic neuropathy using a cutoff of 205 mmHg.s‐1 (Sensitivity 100%, specificity 86%, PPV92%, NPV100%). Conclusions & Inferences PBAUC1 is increased in multiple colonic segments in neuropathic pediatric STC and constitutes a sensitive and specific biomarker of neuropathy.